2019
DOI: 10.1186/s13293-019-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Female sex, high soluble CD163, and low HDL-cholesterol were associated with high galectin-3 binding protein in type 1 diabetes

Abstract: BackgroundGalectin-3 binding protein (Gal3BP), sCD163, galectin-3, and depression have been linked to cardiovascular disease and mortality. In patients with type 1 diabetes, female sex has also been linked to cardiovascular disease and mortality. The aim was to explore whether female sex, sCD163, galectin-3, and depression were associated with Gal3BP in patients with type 1 diabetes. We adjusted for metabolic variables, creatinine, smoking, physical inactivity, and cardiovascular disease.MethodsCross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…This finding was in line with data from previous in vivo and in vitro studies that showed increased expression of Gal-3BP in different phenotypes of metabolic syndrome, including nonalcoholic fatty liver disease, obesity and silent atherosclerosis [16,17]. However, in contrast to some previous studies, our data failed to show a significant correlation between Gal-3BP and clinical lipid profiles or age in women after menopause [9,18]. This may be due to differences in study subjects owing to the selective inclusive criteria and may imply that Gal-3BP is more associated with adipose dysfunction than with fat deposition [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding was in line with data from previous in vivo and in vitro studies that showed increased expression of Gal-3BP in different phenotypes of metabolic syndrome, including nonalcoholic fatty liver disease, obesity and silent atherosclerosis [16,17]. However, in contrast to some previous studies, our data failed to show a significant correlation between Gal-3BP and clinical lipid profiles or age in women after menopause [9,18]. This may be due to differences in study subjects owing to the selective inclusive criteria and may imply that Gal-3BP is more associated with adipose dysfunction than with fat deposition [19].…”
Section: Discussionsupporting
confidence: 89%
“…Recently, several clinical investigations have suggested that Gal-3BP is related to metabolic dysfunctions ranging from nonalcoholic fatty liver disease to atherosclerosis [5][6][7]. However, few studies have focused on the relationship between insulin resistance and Gal-3BP, and the results remain controversial [8,9]. For this reason, we conducted this study focused on the associations between Gal-3BP and insulin homeostasis and the relevance of Gal-3BP as a biomarker of insulin resistance in the menopausal population.…”
Section: Introductionmentioning
confidence: 99%
“…HDL-cholesterol is a well-known predictor for CV disease, but the role of HDL-cholesterol as a causal factor in CV disease is disputed [27]. HDLcholesterol levels have recently been shown to decrease secondary to inflammatory states [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Lower HDL-cholesterol levels have been demonstrated secondary to inflammatory states [25,26], and are well-known predictors for CV disease [27].…”
Section: Introductionmentioning
confidence: 99%
“…The study has a cross sectional design, and is one of several studies addressing metabolic and inflammatory disturbances in a cohort of patients with T1D [24][25][26][27][28][29][30]. For inclusion and exclusion criteria, number of included and excluded patients, and missing variables, see Fig.…”
Section: Methodsmentioning
confidence: 99%